EVALUASI KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA MENGGUNAKAN METODE RGEC DAN ISLAMICITY PERFORMANCE INDEX (IPI) - Wiwin Yulistiani; Nurul Haq; Faisal Muttaqin (J-EBI (Jurnal Ekonomi Bisnis Islam), 2023)
ABSTRACT This study aims to determine the financial performance of Islamic banking in Indonesia using the RGEC method and the Islamicity Performance Index.To find out this, researchers used a descriptive quantitative method with secondary data collection techniques in the form of financial reports that are available on the official website of each Islamic bank for the 2017-2021 period. The samples used were 5 Islamic Banks. The results of financial performance research using the REC method (Risk Profile, Earnings and Capital), namely NPF, FDR, BOPO and CAR show that the five banks are in good condition. However, the Earnings ratio (ROA) of Bank Muamalat Indonesia is considered Not Good with an average percentage of 0.04% and the other four banks are considered Fairly Good with an average percentage of ≥0.05%. The results of the research on financial performance using the Islamicity Performance Index method on the Profit Sharing Ratio show that the four Islamic banks are in good condition and Bank BTPN Syariah is in a bad condition with an average percentage of 0.024% less than 30%. The Zakat Performance Ratio and Equitable Distribution Ratio of the five Islamic banks are stated to be very unfavorable. In Islamic Investment vs. Non-Islamic Investment and Islamic Income vs. Non-Islamic Income, the five Islamic banks are stated to be very good with an average percentage of ≥50.Keywords: Evaluation, RGEC, Islamicity Performance Index